Effect of triple-frequency sono-germination and soaking treatments on techno-functional characteristics of barley - Tabussam Tufail; Huma Bader Ul Ain; Jawad Ashraf; Muhammad Safiullah Virk; Zahoor Ahmed; Mokhtar Dabbour; Tawfiq Alsulami; Suleiman Althawab; Bin Xu (Ultrasonics Sonochemistry)
This research aimed to evaluate the effect of triple-frequency ultrasound treatment (TFUT), germination (GE), and traditional soaking (TS) methods on the nutritional and techno-functional properties of two different barley varieties, including ZQ2000 and XMLY22. Both ZQ2000 and XMLY22 varieties exhibited the highest total phenolic content (TPC) with 840.73 ± 23.59 μg of GAE/g DW and 720.33 ± 30.56 μg of GAE/g DW, and total flavonoid content (TFC) with 520.79 ± 23.45 μg of QUE/g DW and 420.84 ± 19.80 μg of QUE/g DW, respectively. Enzyme activities, such as peroxidase (POD) and polyphenol oxidase (PPO), were notably elevated, indicating enhanced defense mechanisms. The study also found increased γ-Aminobutyric Acid (GABA) levels and antidiabetic potential through inhibition of α-amylase and α-glucosidase enzymes. Further, gene expression analysis revealed differential regulation of phenylpropanoid pathway genes, contributing to the bioactive compound enhancement. Strong intermolecular interactions were observed in both ZQ2000 and XMLY22 samples subjected to TFUT, GE, TFUT + GE, and TS, as validated by FTIR and molecular docking analyses. The structural configuration of two barley types, ZQ2000 and XMLY22, was determined using Fourier transform infrared (FTIR) spectroscopy, which indicated an increase in α-helix and β-sheet conformation and a decrease in random coil conformation in samples treated with TFUT + GE. Moreover, SEM observation provides convincing evidence that TFUT + GE improves and speeds up the breakdown of ZQ2000′s internal structures. Conclusively, this study suggests that the combination of ultrasound and germination treatments significantly enhances the functional properties of barley, making it a promising method for creating health-enhancing barley-based products offering potential applications in functional food development.